Proteolytic Processing of CD44 and Its Implications in Cancer - Priscila Anhel Medrano-González; Osmar Rivera-Ramírez; Luis Felipe Montaño; Erika P. Rendón-Huerta (Hindawi Limited, 2021)
CD44 is a transmembrane glycoprotein expressed in several healthy and tumor tissues. Modifications in its structure contribute differently to the activity of this molecule. One modification that has provoked interest is the consecutive cleavage of the CD44 extracellular ectodomain by enzymes that belong mainly to the family of metalloproteases. This process releases biologically active substrates, via alternative splice forms of CD44, that generate CD44v3 or v6 isoforms which participate in the transcriptional regulation of genes and proteins associated to signaling pathways involved in the development of cancer. These include the protooncogene tyrosine-protein kinase Src (c-Src)/signal transducer and activator of transcription 3 (STAT3), the epithelial growth factor receptor, the estrogen receptor, Wnt/βcatenin, or Hippo signaling pathways all of which are associated to cell proliferation, differentiation, or cancer progression. Whereas CD44 still remains as a very useful prognostic cell marker in different pathologies, the main topic is that the generation of CD44 intracellular fragments assists the regulation of transcriptional proteins involved in the cell cycle, cell metabolism, and most importantly, the regulation of some stem cell-associated markers.